Cultivating knowledge: design and development of the infographic (baja sawit) mobile application to enhance oil palm fertilization practices among smallholders - Ishak, Azura; Murdi, Ahmad Afandi; Hashim, Khairuman; Muhammed, Abdullah; Rahmat, Masura; Shahrani, Shahrina; Abd Rahman, Rohizah; Zainal, Noor Faridatul Ainun; Abd Aziz, Nordiana (Faculty of Engineering, Chulalongkorn University, 2024)
This study presents detailed information for developing the Infographic Oil Palm Fertilize Mobile Application called Baja Sawit. The Infographic Baja Sawit Mobile Application development aims to promote good practices in palm fertilization among smallholders in a simple and accessible manner using Mayer's 12 Principles of Multimedia Learning approach. The study illustrates the systematic development of the application's content, marked by precision in integrating insights derived from a comprehensive literature analysis and interviews with five highly skilled professionals in oil palm fertilizers. The workshop done with the Malaysian Palm Oil Board (MPOB) used the Infographic Baja Sawit App, monitoring participants throughout. This study utilized the Mobile Application Development Life Cycle (MADLC) methodology, encompassing seven key phases: identification, design, development, prototyping, testing, deployment, and maintenance. The resulting Infographic Baja Sawit Mobile Application offers substantial advantages to oil palm smallholders by actively promoting best practices in palm fertilization. This study has substantial implications for developing a digital information infographic culture tailored to oil palm smallholders from various regions in Malaysia.